(3JdNjU GdeaJGMs - (3LeTjO Hf SYhO , LeTjO Hf eSYhO Hf eMehO Hf eMehO GdcGTGfj, ZjGK GdOjf,J (B832 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO CeG HYO jbhd deG aQZJ ef JMQjQ cJGHi GdeSei HeaJGM GdMSGH hgh bQjH KeGfjI CeKGd gPG GdcJGH aGfJNHJ efg gPG GdeNJUQ s
(3BNQgG (B:s
(3hdMGUd VQH GdCKfjf GdPi gh LPQ GdCQHYI ai KdGKI GdPi gh LPQ GdJSYI dCfg CjVkG hdfNJe GdcdGe ggfG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B158s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1760s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs